Euphoria fashion - Bivens, Heidi 1976- (A24 Films LLC, 2022)
"Strip down and slip into Euphoria Fashion, Heidi Bivens' encyclopedia of fabricated fantasy. From the micro mini-skirts worn in the halls of Euphoria High to the maximalist theater of house party outfits, Euphoria Fashion is about more than just costumes - it's a guide in understanding that clothes are the conduit."--A24 website
"Featuring: Maude Apatow, Angus Cloud, Alexa Demie, Jacob Elordi, Barbie Ferreira, Hunter Schafer, Sydney Sweeney, Zendaya"--Page 4 of cover
Keywords: Euphoria -- Fernsehsendung; Kostüm; Euphoria (Television program) / Miscellanea; Costume; Costume design; Costume / (OCoLC)fst00880759; Costume design / (OCoLC)fst00880794; Trivia and miscellanea / (OCoLC)fst01921748; Bildband